2006
DOI: 10.1038/sj.bjc.6603381
|View full text |Cite
|
Sign up to set email alerts
|

Are microRNAs located in genomic regions associated with cancer?

Abstract: We report on the location of 283 miRNAs in the human genome in relation to copy number changes in three distinct types of tumours: prostate, bladder and colon. In prostate and colon tumours, we find miRNAs over-represented in regions with copy number gain and under-represented in regions with copy number loss. Surprisingly this pattern appears to be reversed in bladder cancer. We compared our miRNA copy number data to published miRNA expression data; unexpectedly, we did not find a statistically significant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 17 publications
2
21
0
4
Order By: Relevance
“…The majority of published studies which have evaluated the global microRNA expression pattern of colon tumors indicate that more microRNAs show increased expression in colon cancer compared to those that have reduced expression 5, 8-10 . These observations are consistent with findings that microRNA locations are over-represented in regions of genomic copy number gain and under-represented in regions of copy number loss in colon cancer 11, 12 . While the meaning of this is unclear, there may be more oncogenic microRNAs than tumor suppressor microRNAs in colon cancer.…”
Section: Microrna Expression Patterns Are Altered In Colon Tumorssupporting
confidence: 92%
“…The majority of published studies which have evaluated the global microRNA expression pattern of colon tumors indicate that more microRNAs show increased expression in colon cancer compared to those that have reduced expression 5, 8-10 . These observations are consistent with findings that microRNA locations are over-represented in regions of genomic copy number gain and under-represented in regions of copy number loss in colon cancer 11, 12 . While the meaning of this is unclear, there may be more oncogenic microRNAs than tumor suppressor microRNAs in colon cancer.…”
Section: Microrna Expression Patterns Are Altered In Colon Tumorssupporting
confidence: 92%
“…Lamy et al reported that miRs in BC are over-represented in regions of copy number loss [44]. Tatarano et al demonstrated that deletion of 4p15.31, which is commonly observed in BC cell lines, results in the loss of tumor suppressor miR-218, and restoration of miR-218 expression inhibits BC proliferation, migration, invasion, and apoptosis [45].…”
Section: Resultsmentioning
confidence: 99%
“…The causes of miR deregulation in tumors are not well known but may include gene dosage alterations or rearrangements close to miR loci (9,(39)(40)(41). In this study, we investigated a series of miRs mapped to chromosomal regions frequently altered in MCL (14).…”
Section: Discussionmentioning
confidence: 99%